Humanização, educação musical e escola: processos educativos no Musical de Evangelização Santo Agostinho - Previato, Daniel Bianconi (Universidade Federal de São Carlos, 2021)
This thesis, qualitative and characterized as a case study, had the Musical of Evangelization Saint Augustine as its object of study, an artistic-musical event promoted by a non-profit, Catholic confessional, primary education school that assist students from Early Childhood Education, Elementary School, and High School and whose realization happened throughout 2018. From a core theme (Saint Augustine), each class made studies and productions about a specific subtopic that culminated in an artistic performance shown at two nights of presentations at the end of the school year. It was the consequence of collective work that counted on the activity participation of teachers, direction, coordination, school staff, parents and other family members of students, and school community volunteers. Admitting this event as a social practice and based on the idea that educational processes emerge from every social practice that, in turn, promote transformations in the life of who experience them, the question that motivated this doctorate research was: what educational processes and human happen changes during an artistic-musical event executed by a school and in which the school community participates collaboratively? Therefore, the aim was to comprehend educational processes and human transformations that resulted from participation in the event. Data arise from the participant observation, collective semi-structured interviews with students and teachers, and an individual semi-structured interview with a student’s mother who also helped as a volunteer. The data registration occurred through a filed diary, simple reports written by some students who wished to do it after the interviews, photos, videos, and audio recordings. The analyses happened using the procedure of content analysis, guided by a group of authors, each within their specific theme, capable of embracing the different issues that emerged from it, in a dialogical manner and with humanization as a horizon. The result revealed sundry educational processes organized into three categories: 1 – theoretical and bibliography; 2 – oriented to the acquisition and development of technical abilities; 3 – oriented to the human formation. Each one of these categories kept itself many educational processes that indicated significant changes in the lives of those involved. Thereby, it was possible to perceive the singular importance of school events that provide the engagement of all those who constitute the school routine and of the community assisted by it and the value that music and different artistic manifestations have in the development of social practices, educational processes, and human transformations. Lastly, this thesis still provides ways and raises new questions and possible sequences of studies about this theme.
Humanization, music education, and school: educational process in the Musical of Evangelization Saint Augustine
Keywords: Educação escolar humanizadora; Práticas sociais e processos educativos; Educação musical; Humanização; Interdisciplinaridade; Humanizing education at school; Social practices and educational processes; Music education; Humanization; Interdisciplinarity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO